Meiotic studies in Dysdercus Guérin Meneville, 1831 (Heteroptera: Pyrrhocoridae) : II. Evidence on variations of the diffuse stage between wild and laboratory-inbred populations of Dysdercus chaquensis Freiberg, 1948 - Bressa, María José (2002)
Dysdercus Guerin Meneville, 1831 comprises insect species that are often serious pests of cotton both in the Old and New World, representing the only taxon from Pyrrhocoridae in the Neotropical Region. The genus is cytologically characterized by possession of holokinetic chromosomes and a prereductional type of meiosis. So far, only seven species from the Old World and five species from the Neotropical Region have been cytogenetically described. In the present report we compare the male meiosis from both natural and inbred populations of Dysdercus chaquensis Freiberg, 1948. Our results demonstrated that even though both populations share the same diploid chromosome number, the presence of a diffuse stage was found to be committed to the wild population of the species. Furthermore, the diffuse stage was found in a high frequency in all analysed wild specimens, indicating the long duration of this period among the regular meiosis of D. chaquensis. Taking into account that the diffuse stage is connected with an intense and long period of cellular growth, and with an important transcriptional activity, the absence of this stage in all the inbred specimens of D. chaquensis could be related with the lack of unfavourable physiological conditions due to the environmental uniformity along seven years of inbreeding.